2020
DOI: 10.1126/sciadv.aaz7808
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the translesion synthesis polymerase REV1 exploits replication gaps as a cancer vulnerability

Abstract: The replication stress response, which serves as an anticancer barrier, is activated not only by DNA damage and replication obstacles but also oncogenes, thus obscuring how cancer evolves. Here, we identify that oncogene expression, similar to other replication stress–inducing agents, induces single-stranded DNA (ssDNA) gaps that reduce cell fitness. DNA fiber analysis and electron microscopy reveal that activation of translesion synthesis (TLS) polymerases restricts replication fork slowing, reversal, and for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
106
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(111 citation statements)
references
References 73 publications
5
106
0
Order By: Relevance
“…Not surprisingly, TLS confers chemotherapy resistance, is a cancer adaptation, and is actively being targeted for cancer therapy (53,54). Moreover, we find that replication gaps due to BRCA deficiency is the basis for synthetic lethality to PARP inhibitors (55).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Not surprisingly, TLS confers chemotherapy resistance, is a cancer adaptation, and is actively being targeted for cancer therapy (53,54). Moreover, we find that replication gaps due to BRCA deficiency is the basis for synthetic lethality to PARP inhibitors (55).…”
Section: Discussionmentioning
confidence: 83%
“…It will also be critical to identify gap filling mechanisms that can be targeted to restore hypersensitivity; one possible target is translesion synthesis (TLS). Indeed, CHD4 depletion elevates TLS that suppresses replication gaps (21,39,53).…”
Section: Discussionmentioning
confidence: 99%
“…However, since DNA damage is not induced in ER stress-adaptive cells, it remains unclear how the activity of polymerase η in stress-adaptive cells is promoted. Notably, several recent studies uncovered that PCNA was ubiquitinated even in the absence of DNA damage to recruit translesion synthesis polymerases for completion of DNA replication [ 68 , 69 , 70 ]. Thus, delayed progression of S phase and cell-cycle transition in stress adaptive cells can serve as the contributing factors to the increased activity of polymerase η, consequently accounting for the enhanced resistance of these cells to cisplatin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Distinguishing between these two possibilities will require further analysis but it has previously been shown that DNA replication genes can be up-regulated as an adaptive response to replication stress. Indeed, replication stress reduces cell fitness of cancer cells, and several adaptive mechanisms have been described including upregulation of translesion synthesis (TLS) or replisome components (Bianco et al, 2019;Nayak et al, 2020). Bianco et al, reported over-expression of Timeless, Claspin and Chk1 in various cancers, and showed that tolerating oncogene-induced replication stress was accompanied by overexpression of DDR genes and genes involved in fork protection.…”
Section: Discussionmentioning
confidence: 99%